Marketing Management and Communications in the Public Sector - Pasquier, Martial; Villeneuve, Jean-Patrick (2018)
This updated edition of Marketing Management and Communications in the Public Sector provides a thorough overview of the major concepts in public sector marketing and communications, two fields that have continued to grow in importance for modern public administrations. With extended coverage of topics such as social marketing and institutional communication, the authors skilfully build on the solid foundations laid down in the previous edition. Replete with real-world case studies and examples, including new material from the USA, Australia, and Asia, this book gives students a truly international outlook. Additional features include exercises and discussion questions in each chapter and an illustrative extended case study. This refreshed text is essential reading for postgraduate students on public management degrees, and aspiring or current public managers. The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9781315622309, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.
English
Keywords: Business & management; Business communication & presentation; Sales & marketing; Public relations; Non-profitmaking organizations; Political economy; Public administration; Central government policies; communication ethics; communication models; communication strategies; communication theory; co-branding; crisis communication; Jean-Patrick Villeneuve; marketing instruments; non-profit management; public administration; public communication; public management; public marketing; public sector marketing; public-private partnerships; social marketing